Community pharmacist counselling practices in the Bisha health directorate, Saudi Arabia -simulated patient visits - Hassan Al Qarni; Tahani Alrahbini; Ayidh M AlQarni; Abdullah Alqarni (BMC, 2020)
Abstract Background Many organizations have suggested a minimum standard regarding pharmaceutical counselling for patients, which includes information about the name of the drug, the description the drug, the indication for use, how to use it, the method of treatment, precautions, adverse reactions, and any contraindications. Correspondingly, the World Health Organization (WHO) has recommended that pharmacists spend at least 3 min with each patient to provide counselling. This study aimed to evaluate the counselling practices of community pharmacists for both over-the-counter (OTC) and prescription-only medicines in the Bisha Health Directorate, Saudi Arabia. Method This was a cross-sectional study designed to evaluate simulated patient visits to observe real counselling practices of community pharmacies in the Bisha area; 73 pharmacies were visited. Two scenarios were used in this study. The first scenario was for a prescription-only medicine, and the second scenario was for an OTC medicine. The duration of counselling was recorded for every visit. Results A total of 105 visits to the 73 pharmacies were conducted under the following scenarios: scenario 1 = 73 visits and scenario 2 = 32 visits. The average time for the simulation was 110 s for scenario 1 and 73.4 s for scenario 2. There was a statistically significant negative correlation between the duration of counselling and patient simulation visits that occurred in the morning (Spearman's rho = − 0.396, p = 0.001). Conclusion It was shown that patient counselling needs to be given greater emphasis in community pharmacies. In this study, the time spent for patient counselling failed to meet the minimum WHO standard. Thus, pharmacists must be encouraged to spend at least 3 min on patient counselling.